Factors Affecting the Quality of Life of the Elderly in Iraq and Turkiye and Differences Between the Two Cultures - Tahsin Barış Değer; Hatem Al Yasarı (Journal of Economy Culture and Society)
The aim of this study was to determine the quality of life (QOL) of the elderly living in Iraq and Turkiye and the effect of sociodemographic, health, economic, lifestyle and spiritual factors on the QOL in the elderly cross-culturally. The study was conducted with a total of 200 participants aged ≥65 years in Iraq and Turkiye with face-to-face interviews. The WHOQOL-OLD scale was used. Comparison tests for univariate group rank values were used to compare total scale scores. The mean total score for QOL was 77.70 ± 11.40 in Turkiye, and 65.47 ± 7.20 in Iraq. In Iraq, factors affecting low QOL were age 85 years and older, female gender, being single, low educational level, not having a regular salary, insufficient income, chronic disease, drug use and disability. Factors effective on high QOL were eating healthily, walking or exercising regularly, praying five times a day, and reading the Qur'an in Iraq. Factors affecting high QOL in Turkiye were having another income outside of a salary, not having chronic diseases, having a healthy diet, walking or exercising and thanking God. QOL was higher in older participants in Turkiye than those in Iraq.